Analysis of indole derivatives in methanolic extracts from mycelium of Agaricus bisporus cultured in vitro on liquid Oddoux medium - Muszyńska, Bożena; Sułkowska-Ziaja, Katarzyna; Hałaszczuk, Patrycja; Krężałek, Remigiusz; Łojewski, Maciej (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
Methanolic extracts obtained from biomass of Agaricus bisporus (J.E. Lange) Imbach cultured in vitro were analyzed for qualitative and quantitative composition of non-hallucinogenic indole compounds in order to compare their amount with fruiting bodies of these species. Extracts demonstrated to contain six indole compounds. Contents of individual compounds ranged from 0.01 to 21.33 mg/100 g d.w. in biomass from in vitro cultures. The quantitatively dominating compounds included: 5-hydroxytryptophan (12.50 mg/100 g d.w.), L-tryptophan (14.00 mg/100 g d.w.) and serotonin (7.00 mg/100 g d.w.). Total content of the remaining indole compounds under analysis in the study was 55.32 mg/100 g d.w.